2021
DOI: 10.1108/jbim-04-2020-0204
|View full text |Cite
|
Sign up to set email alerts
|

Multichannel integration through innovation capability in manufacturing SMEs and its impact on performance

Abstract: Purpose Using online channels is an opportunity for small and medium-sized enterprises (SMEs) in the manufacturing industry to reach new markets and reduce the dependency on distributors. The challenge remains that of integrating new online channels into existing networks effectively. This paper aims to identify to what extent multichannel integration is enhanced by the innovation capability of manufacturing SMEs and the subsequent influence on their performance. Design/methodology/approach Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 84 publications
2
17
0
Order By: Relevance
“…For example, Luo et al (2016) found firms with more IT applications or that invest in a more balanced portfolio of IT applications can develop stronger cross-channel capabilities. Meanwhile, Cao and Li (2018) identified IT capability as a technology-related factor that can positively affect and Kolbe et al (2021) found manufacturing SMEs with advanced technological capabilities can achieve higher levels of multichannel integration. Saghiri and Mirzabeiki (2021) demonstrated advanced information and digital technologies can enhance omni-channel data flow integration.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…For example, Luo et al (2016) found firms with more IT applications or that invest in a more balanced portfolio of IT applications can develop stronger cross-channel capabilities. Meanwhile, Cao and Li (2018) identified IT capability as a technology-related factor that can positively affect and Kolbe et al (2021) found manufacturing SMEs with advanced technological capabilities can achieve higher levels of multichannel integration. Saghiri and Mirzabeiki (2021) demonstrated advanced information and digital technologies can enhance omni-channel data flow integration.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This research follows previous research saying that the relationship between supply chain partners improves innovation capability in the manufacturing industry. In practice, for example, the SCI, namely collaboration with partners based on trust, can affect IC; namely, companies can be the first in product development in the market (Kolbe et al, 2021;(Jimenez-Jimenez et al, 2019).…”
Section: Results Interpretationmentioning
confidence: 99%
“…Supply chain integration positively impacts innovation capability (Kolbe et al, 2021). Collaboration with the customers and suppliers enables the company to create a new product (Jimenez-Jimenez et al, 2019).…”
Section: Influence Supply Chain Integration On Innovation Capabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Online retail channels aim to attract consumers and increase their demand for their products through new marketing strategies (Kolbe et al , 2022). However, several e-commerce firms faced high returns rates because of inaccurate and incomplete product information on their sites (Vasić et al , 2019).…”
Section: Introductionmentioning
confidence: 99%